LEVERS OF CONTROL, MANAGEMENT INNOVATION AND ORGANIZATIONAL PERFORMANCE IN HEAVY EQUIPMENT AND TRUCK COMPANIES IN NORTH KALIMANTAN - Chandra, Rita; Ismail, Tubagus; Norhamida, Hana (JURNAL EKBIS, 2025)
This study aims to evaluate the crucial role of management control systems on organizational performance, by adopting the levers of control framework developed by Simons (1994). The sample in this study consisted of employees who held supervisory positions in heavy equipment and truck companies operating in the North Kalimantan region. The sampling technique used the purposive sampling method by distributing questionnaires to related companies, and succeeded in obtaining 57 respondents. Hypothesis testing was conducted using the PLS-SEM approach. The results of the analysis showed that enabling control has a direct effect on organizational performance, while constraining control has an indirect impact. In addition, management innovation has been shown to have a direct effect on organizational performance, and is a mediator in the relationship between constraining control and organizational performance.